The impact of COVID-19 quarantine on lifestyle indicators in the United Arab Emirates - AlBlooshi, Sharifa; AlFalasi, Maryam; Taha, Zainab; El Ktaibi, Farid; Khalid, Alia (Frontiers in Public Health, 2023)
Abstract COVID-19 is a virus that has spread globally and brought an economic and social crisis to numerous countries. The current study aimed to investigate the impact of COVID-19 quarantine on dietary habits, physical activity, food purchasing, smoking, and sleeping patterns in the United Arab Emirates. This study aimed to investigate the impact of COVID-19 quarantine on the dietary habits and physical activity of UAE citizens. A cross-sectional study was conducted using an online questionnaire between November 1st, 2020 and the end of January 2021. Participants were asked to complete an anonymous electronic questionnaire created via Google Forms and distributed on various platforms, such as WhatsApp, Twitter, and email. A total of 1682 subjects participated in the study. The results included that during the COVID-19 lockdown, more participants (44.4%) reported an increase in weight. This gain seems to be linked to increased food consumption (Adjusted Odd Ratio) AOR = 1.68, 95% (Confidence Interval) CI = 1.12, 2.54), decreased physical activity (AOR = 2.25, 95% CI = 1.58, 3.21), and increased smoking (AOR = 1.90, 95% CI = 1.04, 3.50). The groups that were most likely to gain weight included those who consumed more cereals (AOR = 1.67, 95% CI = 1.08, 2.57), had an increased desire for sweets (AOR = 2.19, 95% CI = 1.50, 3.19), and an increased desire for food (hunger) (AOR = 2.19, 95% CI = 1.53, 3.14). In contrast, those who exercised more were more likely to lose weight (AOR = 0.61, 95% CI = 0.44, 0.86) as well as those who slept over 9 hours a day (AOR = 1.90, 95% CI = 0.45, 0.88). Overall, it is essential to promote healthy habits and methods of healthy diet maintenance during stressful and unusual times when people might find it difficult to put effort into their health.